Central bank communication: Managing expectations through the monetary dialogue - Ansgar Belke (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
Successfully managing a course back to normality ("exit") will depend crucially on the central banks' ability to communicate effectively a credible strategy for an orderly exit from such kind of policies. In this context, clear, deliberate, coordinated messages that are anchored in the central banks' mandate are essential. We focus upon transparency and "forward guidance" as potential tools to stimulate the economy in the Euro Area. We then deliver details on whether and how the effectiveness of central bank's policies can be improved through more transparency and "forward guidance". We do so by highlighting marked differences in the Fed's and the ECB's interpretation of "forward guidance". In order to highlight the key issues of central bank communication and the management of expectations referring to a practical institutional example, we also comment on the role of the Monetary Dialogue, i.e. the regular appearances of the President of the European Central Bank (ECB) before the European Parliament (EP), in the context of an evolving monetary policy. Communication is finally described as a policy option in terms of minimising risk in the context of exit from unconventional monetary policies and of the signalling channel which refers to what the public learns from announcements of unconventional monetary policy operations such as Quantitative Easing. – – Dieser Beitrag untersucht eine Reihe von wichtigen Fragen bezüglich der Transparenz und der Rechenschaftslegung von Zentralbanken. Dabei wird besonderes Gewicht auf den sogenannten Monetären Dialog, d.h. das regelmäßige Erscheinen des EZB-Präsidenten zu Kommunikationszwecken vor dem Europäischen Parlament, gelegt. Um die Kernaspekte der Kommunikation und des Erwartungs-Managements von Zentralbanken zu beleuchten, bezieht er sich auf ein praktisches institutionelles Beispiel, den "Monetary Dialogue" im Kontext einer sich entwickelnden neuen unkonventionellen Geldpolitik. Kommunikation wird als eine geldpolitische Politikoption zur Minimierung von Risiken beschrieben, die im Kontext des Ausstiegs aus der unkonventionellen Geldpolitik entstehen können. Darüber hinaus wird sie als ein praktischer Bestandteil des Signalling-Kanals interpretiert. Dieser beschreibt, was die Öffentlichkeit aus den Ankündigungen unkonventioneller geldpolitischer Maßnahmen wie der quantitativen Lockerung (QE) lernt.
Keywords: E52; E58; G14; 330; central bank communication; European Central Bank; forward guidance; monetary dialogue; transparency